Inventory Management Methodology to determine the levels of integration and collaboration in supply chain (2017)
This paper presents a Methodology of Inventory Management that determines the levels of integration and cooperation in a supply chain, so that policies and joint actions to improve the performance of the actors in the chain strategies are generated. It defined the five steps to implement collaborative planning between actors in the supply chain and integration of processes within the same processes as well as indicators to measure their performance as a result of a monitoring strategy. The methodology is validated in Wood sector companies of the city of Barranquilla, where weaknesses are evident in inventory management because they have not adopted best practices for managing inventories collaboratively between actors from different levels Supply Chain. The results show low levels of integration of inventory management processes within companies, which is the result of poor collaboration and integration process between actors from different levels of the supply chain of wood and furniture, allowing to define strategies to improve inventory management among companies that comprise it. © 2017, Universidad de Tarapaca. All rights reserved.